PENINGKATAN MOTIVASI DAN HASIL BELAJAR GEOGRAFI MATERI POSISI STRATEGIS INDONESIA SEBAGAI POROS MARITIM DUNIA MENGGUNAKAN MEDIA POWERPOINT BERBASIS APLIKASI GOOGLE CLASSROOM PADA SISWA KELAS XI IPS-1 SMA NEGERI 1 SIBORONGBORONG SEMESTER 1 TAHUN PELAJARAN 2021/2022 - Anna Simanjuntak (Jurnal Sabilarrasyad, 2021)
This research is motivated by the low motivation and learning outcomes of students in learning material Characteristics of land and water areas in Indonesia in class XI IPS-1 SMA Negeri 1 Siborongborong. The purpose of this study is to increase student activity and learning outcomes by using powerpoint media based on the google classroom application. This study uses Classroom Action Research with a cycle consisting of 4 stages, namely planning, implementation, observation, and reflection. The research subjects were students of class XI IPS-1 SMA Negeri 1 Siborongborong Semester 1 of the Academic Year 2021/2022 with a total of 36 students. Techniques and data collection tools using test and non-test techniques (observation and documentation). The data analysis method in this study used qualitative data analysis. The results showed an increase in learning motivation from 9 students or 25.00% in the initial study to 24 students or 66.67% in the first cycle and 33 students or 91.67% in the last cycle. This is supported by an increase in the average initial study learning outcome of 56.11, in the first cycle the average score obtained by students is 72.50 and in the second cycle the average score obtained by students is 82.78 and is supported by an increase in complete learning in the initial state as many as 7 students (19.44%), in the first cycle increased to 19 students or 52.78% and in the second cycle increased back to 32 students or 88.89%. From the acquisition of the figures above, it can be concluded that in the second cycle, the process of implementing learning improvements was declared successful and complete in the second cycle